2019
DOI: 10.1002/pssr.201800551
|View full text |Cite
|
Sign up to set email alerts
|

Electric‐Field Control of Dirac Two‐Dimensional Electron Gas in PbTe/CdTe Heterostructures

Abstract: Two‐dimensional electron gases (2DEGs) confined to quantum wells trigger rich emergent phenomena and serve as a host for high‐speed electronics. 2DEG in PbTe/CdTe heterostructure was predicted to be Dirac electrons and confirmed by recent experiments. Here, we demonstrate the manipulation of electrical transport properties of this 2DEG with extremely high mobility and unique electron structure by ionic liquid‐gating. The extreme capacitance of carrier modulation enables to tune the band structure. With a chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The CdTe/PbTe heterojunction system, consisting of zincblende CdTe and rocksalt PbTe, was recently found to exhibit a two-dimensional electron gas (2DEG) at the (111) polar interface with exceptional carrier density and mobility. The 2DEG is attributed to the interfacial bonding coordination mismatch, which is different from traditional 2DEG systems [ 8 , 9 , 10 , 11 ]. The authors [ 12 , 13 ] showed that such a system was a good candidate for high-speed mid-infrared detectors.…”
Section: Introductionmentioning
confidence: 99%
“…The CdTe/PbTe heterojunction system, consisting of zincblende CdTe and rocksalt PbTe, was recently found to exhibit a two-dimensional electron gas (2DEG) at the (111) polar interface with exceptional carrier density and mobility. The 2DEG is attributed to the interfacial bonding coordination mismatch, which is different from traditional 2DEG systems [ 8 , 9 , 10 , 11 ]. The authors [ 12 , 13 ] showed that such a system was a good candidate for high-speed mid-infrared detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have investigated the mechanism of conduction between the insulating non-polar STO and different polar layers, like LaTiO 3 /STO, PrAlO 3 /STO, NdAlO 3 /STO, GdTiO 3 /STO, and LaGaO 3 /STO [15][16][17][18][19], and nonpolar/nonpolar interfaces [20,21]. Besides, the interfacial transport properties of complex oxides have been modified by different methods, such as modulation doping, gating field, polar adsorbate, and light [22][23][24][25]. Although the response of LaAlO 3 /SrTiO 3 (LAO/STO) to light was investigated many years ago, more recently, the effect of light illumination on the transport properties for different interfaces has revealed the potential applications of these interfaces in electronics and optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%